An exploratory study of integrated reporting: A case of public listed companies in Southeast Asia - Abdullah N.W.; Husin N.M.; Nor M.M. (Serials Publications, 2023)
This exploratory study content analyses the existence of Integrated Reporting (IR) related elements in the corporate reports among top Malaysian and Singaporean public listed companies. As the world begins a long shift toward a higher share of market-based financing, effective disclosure will become even more important. In the future, IR may well play a bigger role. There are significant information gaps in reports, particularly the one conducted within the Southeast Asia setting. Therefore, this study aims to provide exploratory evidence of top Malaysian and Singaporean public limited companies initiative to transform their corporate reports into IR. The evidence suggests that publicly listed companies in both countries have fully converted their corporate report into IR, indicating the support to their respective government initiatives on IR. Serials Publications Pvt. Ltd.